PENERAPAN INOVASI DIGITAL PEMASARAN UNTUK PENINGKATAN OMZET PEMBERDAYAAN EKONOMI RUMAH TANGGA PKK KELURAHAN RAGUNAN - Handayani, Rani Irma; Kristiana, Titin; Setiaji, Setiaji; Listyaningrum, Heni; Aprilia, Sarah (Jurnal AbdiMas Nusa Mandiri, 2024)
The background of this Community Service activity is that PKM partners of PKK cadres in Ragunan Village have several limitations in terms of identity, packaging and product marketing. For product identity, there is no logo (label) for packaging, so the product that has been made is less known. In addition, there is no safe packaging design for the delivery of business products sold. So far, sales have only been carried out through event bazaars around Ragunan village so that there is a lack of marketing networks. Limited sales range, and the target market is not wide and diverse, revenue or sales turnover does not increase. The purpose of this PKM activity is to expand market reach, build strong product appeal, increase sales turnover and increase economic independence. The method for this PKM activity is to provide socialization and training regarding new product logos for the packaging production process on packaging labels, packaging design for shipping packaging, socializing the e-commerce application that has been made to PKK cadres of Ragunan Village. Providing training in using e-commerce platforms to market their products. The targeted output is to create an online sales application (e-commerce) to be able to market the business products of PKK cadres in Ragunan Village widely. This community service reached the main conclusion that digital marketing strategies effectively help the economic empowerment of PKK cadres' households and this strategy shows positive results in increasing their economic independence and income.